Requirements Analysis of Data Center Network Routing Algorithm Based on SDN Architecture - Zifu Fan; Chunling Wu; Jinhong Wang (Dianxin kexue)
With the development of SDN technology, SDN-based data center network will be more extensive. The applications of SDN technology in data center network were focused on; the technical characteristics of modern data center network and SDN technology were analyzed firstly, and a modern data center network architecture based on SDN was designed. Then the requirements of the data center network routing performance based on the SDN were analyzed and summarized and the solutions were proposed in order to provide the reference for the future construction and routing design of the data center network in China.